El procés contra el mulat Amador de Molina per sodomia, del 1588. - NAVARRO, JACOB MOMPÓ (Scripta)
Throughout European history, sodomy has been pursued by civil and ecclesiastical courts. In addition, from 1524 on, the Inquisition obtained jurisdiction to judge sodomy in the territories of Aragon, Catalonia and Valencia. Amador de Molina had been judged and sentenced in Murcia, from where he arrived, exiled, in the village of Ontinyent. Denounced by the rape of a minor, the Court of the Inquisition of Valencia was relentless. Along with the transcription of the process, in this article we provide a general relation of some of the most significant works in the study of the Inquisition and sexual repression, and an outline of the doctrinal and legal frameworks of the sin-crime of sodomy.